Halal Certification Imperatives for MSMEs: Navigating Sustainability, Consumer Confidence, and Policy Compliance (Case of Kenteng, Bandungan, Indonesia) - Rahayu, Sang Ayu Putu; Niravita, Aprila; Anitasari, Rahayu Fery; Kamal, Ubaidillah (Indonesian Journal of Advocacy and Legal Services, 2023)
Micro, Small, and Medium Enterprises (MSMEs) serve as the economic backbone of communities, with their sustainability influenced by various factors, including adherence to business legality. Among the crucial legal aspects, obtaining halal certification stands out as a pivotal requirement. This certification plays a vital role for business entities, aiming to bolster consumer confidence in the products they offer. The research conducted adopts a mixed-methods approach, combining qualitative and quantitative data collection and analysis. Surveys and direct interviews with service partners reveal significant challenges faced by these partners. These challenges encompass a spectrum from comprehending the importance of halal food products and the processes involved in their production to understanding the intricacies of halal certification and the necessary steps to obtain it. In accordance with the Halal Product Assurance regulations, the implementation of halal certification in Indonesia is mandated to expedite. Notably, by no later than October 17, 2024, all products entering, circulating, and trading in Indonesia must be duly halal-certified. This stringent timeline underscores the urgency for businesses to prioritize obtaining halal certification, positioning it as a critical component of their legal obligations. The significance of halal certificates extends beyond mere compliance, serving as a testament to a business's commitment to meeting the ethical and religious considerations of its diverse consumer base. This study also advocates for the important role of halal certification in sustaining MSMEs as the economic backbone of communities. The findings underscore the need for robust policy-making, emphasizing the urgency of halal certification in accordance with Halal Product Assurance regulations in Indonesia. The research aligns with the advocacy for policies that prioritize the timely implementation of halal certification, recognizing it as a critical component for MSMEs to meet legal obligations and enhance consumer trust.